Soil restoration using compost-like-outputs and digestates from non-source-separated urban waste as organic amendments: Limitations and opportunities. (1st February 2020) - Carabassa, Vicenç; Domene, Xavier; Alcañiz, Josep M.
Abstract: Soil rehabilitation in the context of the restoration of quarries, dumping sites, or road slopes often requires the prior addition of organic amendments to improve the substrates used for Technosol construction. Bio-wastes coming from advanced Mechanical-Biological Treatment Plants, mainly compost-like-outputs (CLO) and digestates (DGT), are new and suitable sources of organic matter potentially useful as organic amendments for this purpose, in an approach clearly fulfilling the principles of circular economy. In order to assess the suitability of these materials, a complete physicochemical and biological evaluation was carried out, including an ecotoxicological evaluation to discard hazardous effects on key soil fauna groups. Field experiments were also carried out on several road slopes and a dumping site. The stability degree of organic matter and the impurities content could be restricting parameters for the use of CLO in soils. Low stability degree decreased plant development in the initial stages of restoration. Moreover, the high heterogeneity in terms of physicochemical parameters of the different CLOs assessed is a serious constraint to making generalizations about its use. In contrast, composition of DGTs was more stable between plants and batches, and presented low impurities and high N contents that make them more suitable for applying to soil and promoting plant development. Regarding the application rates, DGT application at 20 g kg −1 clearly improved plant growth after sowing, without compromising recruitment. However, application at 80 g kg −1 did not ameliorate seed germination and plant growth, in either CLO or DGT treatments, and increased N-leaching and toxicity risk to soil mesofauna in DGT amended Technosols. Highlights: CLO and digestates from MBTP are suitable as organic amendments for Technosols. The stability degree and the impurities content of CLO could be restricting parameters for their application to soils. High heterogeneity between batches and production plants hinders making strong generalizations related to the use of CLO. Digestates have a more stable composition and present lower impurities and higher N contents than CLO. Application rates higher than 2% should be avoided. A case per case evaluation should be done before its application at soil.